Excessive addition split peak formed by the non-templated nucleotide addition property of Taq DNA polymerase after PCR amplification - Zhou, Yongsong; Bo, Fan; Tian, Tian; Wu, Buling; Zhu, Bofeng (Frontiers in Bioengineering and Biotechnology, 2023)
Because of its non-template addition feature, Taq DNA polymerase can catalyze one or more extra nucleotides onto the 3′ terminus of PCR products. An extra peak is observed at DYS391 locus after the PCR products stored 4 days at 4 °C. To explore the formation mechanism of this artifact, primers and amplicon sequences of Y-STR loci are analyzed, furthermore, PCR products storage conditions and termination of PCR reaction are discussed. The extra peak is a + 2 addition product, which we call it excessive addition split peak (EASP). The most significant difference between EASP and the incomplete addition of adenine product is that the size of EASP is about one base larger than the true allele and locates on the right side of the real allelic peak. The EASP formation is affected by the primer sequences and the storage conditions of PCR products. The EASP cannot be eliminated by increasing loading mixture volume and conducting heat denaturation prior to electrophoresis injection. However, it is not observed when the PCR reaction is terminated with ethylenediaminetetraacetic acid or formamide. These findings suggest that formation of EASP is a result of 3' end non-template extension by Taq DNA polymerase, rather than being the result of DNA fragment secondary structure produced under a suboptimal electrophoresis condition.